2019
DOI: 10.1093/erae/jbz026
|View full text |Cite
|
Sign up to set email alerts
|

A query theory account of a discrete choice experiment under oath

Abstract: One limitation of stated-preference methods is the formation of hypothetical bias. To address this, the honesty oath has been used as an ex ante technique to reduce hypothetical bias. Our study provides a query account of the honesty oath in a discrete-choice experiment setting by using Query Theory to examine the mechanism behind the effectiveness of the honesty oath. Our results show that the honesty oath can change the content and order of queries; potentially reducing hypothetical bias in discrete choice e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Before formally carrying out the choice experiment, we requested all participants to complete a survey on their socio-demographic characteristics and answer questions related to their perceptions of plant-based meat. To reduce the potential hypothetical bias [ 46 ], an “honest oath” was also included at the beginning of the survey. The respondents were asked to check the following statement before filling out the questionnaire: “I will provide honest answers throughout the experiment”.…”
Section: Methodsmentioning
confidence: 99%
“…Before formally carrying out the choice experiment, we requested all participants to complete a survey on their socio-demographic characteristics and answer questions related to their perceptions of plant-based meat. To reduce the potential hypothetical bias [ 46 ], an “honest oath” was also included at the beginning of the survey. The respondents were asked to check the following statement before filling out the questionnaire: “I will provide honest answers throughout the experiment”.…”
Section: Methodsmentioning
confidence: 99%
“…Stevens et al (2013) have interpreted the solemn oath method "as an implicit contract between the researcher and the respondent" (p. 136). Applications have been reported in open-ended CV surveys (Stevens et al, 2013), dichotomous choice or referendum questions (Jacquemet et al, 2017), auction bidding questions (Jacquemet et al, 2013) and CEs (Carlsson et al, 2017;de-Magistris and Pascucci, 2014;Kemper et al, 2020;Lin et al, 2017;Mamkhezri et al, 2020).…”
Section: Solemn Oathmentioning
confidence: 99%
“…A related approach is based on Query Theory (Johnson et al, 2007), which suggests that preferences are constructed in the moment through a series of successive thoughts, rather than being pre-stored and instantly retrievable, making the final decision depend on the order of the thoughts. Testing this hypothesis, Kemper et al (2020) assessed the differences in thought processes of individuals under oath and observed that an honesty oath changes the content and order of the queries.…”
Section: Solemn Oathmentioning
confidence: 99%
“…Some more recent examples for studies that use revealed preference methods to elicit the WTP for organic products are: Griffith and Nesheim (2010), Briggeman and Lusk (2010), Griffith and Nesheim (2013), Bazoche et al (2013), Waldrop et al (2017). Current references of studies using stated preference methods to elicit the WTP for organic products are: Zander and Hamm (2010), Hu et al (2011), Janssen and Hamm (2012), Rousseau and Vranken (2013), Caputo et al (2013), Gerrard et al (2013, Meas et al (2014), Feldmann and, Zander et al (2015), Kemper et al (2019). Studies that use both stated and revealed preferences to elicit WTP for organic products published in more recent years are rarer: Lusk and Norwood (2009), Brooks and Lusk (2010), Lusk (2011), Gschwandtner (2018).…”
Section: Choice Experiments Designmentioning
confidence: 99%
“…Under Honesty Oath participants make a promise that they are always going to provide truthful answers and evidence supports the ability of this method to reduce hypothetical bias (Jacquemet et al 2009(Jacquemet et al , 2010(Jacquemet et al , 2013. Kemper et al (2019) use Query Theory to explain the mechanism behind the effectiveness of Honesty Oath. They find that Honesty Oath can change the content and order of a query and that Query Theory is a useful tool in order to analyse the thought process in valuation studies.…”
Section: Introductionmentioning
confidence: 99%